Village saving and loans associations transform youth in Uganda - Tukundane, Nelson (Technical Centre for Agricultural and Rural Cooperation, 2018)
In the Kayunga District, the Uganda National Farmers Federation (UNEFFE) and We Effect/Svenska Postkod Lotteriet have been implementing a Village Savings and Loans Association (VSLA) project to increase financial inclusion for young people.